Enhance key generation algorithm based user string identity as public key - Norhidayah, Muhammad (2015)
This study aims to enhance a previous algorithm called the Tripathi algorithm. The Tripathi algorithm proposes an RSA based approach to generate cryptographic keys using a user’s identity, such as an E-mail address. This algorithm uses a user’s identity to replace the numbers that are used as a public key in the RSA algorithm. The main advantage of the Tripathi algorithm is that users can easily recall the public key, since it is their own identity. However, this algorithm is unable to use all of users’ E-mail addresses as public keys, only certain E-mails can be used as public keys. This is due to two main reasons: i) this algorithm uses the same modulo value for every E-mail. Consequently, if the E-mail is not relative prime to modulo value, the new E-mail should be entered, and ii) once the E-mail converted to decimal value, it is composed of odd and even numbers. If the decimal value is in even numbers, then it can’t be used as a public key. Only odd decimal values can be used in a public key using the Tripathi algorithm. Therefore, the Tripathi algorithm needs to be improved so that all E-mail addresses can be used as public keys. The proposed algorithm enables the algorithm to be applicable to all E-mail address domains, such as yahoo, gmail, edu, company, among others.In this study, two experiments were conducted. In the first experiment, an algorithm called the LB-RSA was developed. A looping process was added to this algorithm in order to produce a new modulo value to make the E-mail entered relative prime to the new modulo value, which helps to produce more E-mail addresses that can be used as public keys. This algorithm has shown promising results, and 50% of the total number of E-mails can be used as public keys. This number is greater than the amount generated by the Tripathi algorithm, which is only 10%. Since the result produced by this algorithm did not reach 100%, the second experiment was conducted to further enhance the LB-RSA algorithm. In this experiment, an algorithm called the CLB-RSA was developed. Classifications of decimal values to determine whether the E-mail entered contains odd or even numbers were added to this algorithm. This algorithm achieved 100%, hence, all E-mails considered can be used as public keys.